Categories of (I, I)-Fuzzy Greedoids. (10th November 2015) - Xiu, Zhen-Yu; Shi, Fu-Gui
Abstract : The concepts ofI -greedoids, fuzzifying greedoids, and (I, I )-fuzzy greedoids are introduced and feasibility preserving mappings between greedoids are defined. ThenI -feasibility preserving mappings, fuzzifying feasibility preserving mappings, and (I, I )-fuzzy feasibility preserving mappings are given as generalizations of feasibility preserving mappings. We study the relations among greedoids, I -greedoids, fuzzifying greedoids, and (I, I )-fuzzy greedoids from a categorical point of view.